2010
DOI: 10.1021/jp102730p
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation and Binding Studies of β-Sitosterol with Human Serum Albumin and Its Biological Relevance

Abstract: Beta-sitosterol is a naturally occurring phytosterol that is widely used to cure atherosclerosis, diabetes, cancer, and inflammation and is also an antioxidant. Here, we studied the interaction of beta-sitosterol, isolated from the aerial roots of Ficus bengalensis, with human serum albumin (HSA) at physiological pH 7.2 by using fluorescence, circular dichroism (CD), molecular docking, and molecular dynamics simulation methods. The experimental results show that the intrinsic fluorescence of HSA is quenched by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
84
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(98 citation statements)
references
References 56 publications
14
84
0
Order By: Relevance
“…Thus, the free energy change is−8.5 kcal M −1 at 25°C. These results were fully supported by computational calculation which was obtained as−8.49 kcal M −1 (Table 1) [25][26][27][28]. Further, we performed computational studies like molecular docking and simulations to understand more details of its binding and also stable conformation of protein.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Thus, the free energy change is−8.5 kcal M −1 at 25°C. These results were fully supported by computational calculation which was obtained as−8.49 kcal M −1 (Table 1) [25][26][27][28]. Further, we performed computational studies like molecular docking and simulations to understand more details of its binding and also stable conformation of protein.…”
Section: Resultssupporting
confidence: 63%
“…We have also shown that there are conformational changes in protein due to binding of BA to HSA. Also, it is shown in a recent report from our group on different phytomedicines like maslinic acid, trimethoxyflavone, and coumaroyltyramine, sitosterol, strongly binds to HSA leading to change in protein conformation [25][26][27][28].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…HSA is composed by three homologous a-helical domains (I, II, and III): I (residues 1-195), , and III (384-585), each of which includes 10 helices that are divided into six-helix and four-helix subdomains (A and B) (Sudhamalla, Gokara, Ahalawat, Amooru, & Subramanyam, 2010). The native conformation of HSA has two principal hydrophobic binding sites, called sites I and II (Sudlow, Birkett, & Wade, 1975), located in subdomains IIA and IIIA (He & Carter, 1992) and it is generally assumed that in BSA and HSA these sites are homologous.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence spectroscopy is an effective method to study the interactions between small molecule compounds and proteins [38,39]. The fluorescence spectra of HSA and HSA-PMT mixed solutions are shown in Fig.…”
Section: Characterization Of the Binding Interaction Of Pmt With Hsamentioning
confidence: 99%